Approach to preserve phenolics in Thunbergia laurifolia leaves by different drying treatments. Issue 7 (17th April 2019) - Oh, Hikari Kan Fu; Siow, Lee Fung; Lim, Yau Yan
Abstract: Different drying methods and blanching were investigated as to their effects on antioxidant and oxidase activities of Thunbergia laurifolia leaves. Results showed that oven‐drying had the highest degradation of total phenolic content (TPC) and antioxidant activity at >85%, while freeze‐drying had the lowest at <20%. However, inactivation of oxidase enzymes by blanching at 100°C resulted in a lesser decrease in TPC for oven‐drying at 50 and 100°C (51% and 65%, respectively), indicating the importance of inactivating the oxidase enzymes for lower degradation of phenolics on drying. The high‐performance liquid chromatography analysis showed that its major antioxidant, rosmarinic acid, degraded tremendously in the presence of oxidase enzymes, but only degraded slightly upon inactivation of oxidase enzymes. Hence, this work showed that by controlling the enzymatic activity, the preservation of phenolics with specific bioactivity in herbal tea leaves can be achieved. Practical applications: Thunbergia laurifolia leaves have been frequently consumed in the form of a tea or pill due to its medicinal properties. Processing of fresh herbal plant leaves by drying is required to preserve antioxidant phenolic compounds and quality of the plant leaves. Although the drying effects on the antioxidant properties have been studied, the factors that cause the change in properties have not been investigated in‐depth. Controlling the factors that affect the phenolic content can help to preserve the beneficial antioxidants when processing the leaves by drying. The result of this study will be of relevance and beneficial to the herbal tea industry. Abstract :